2019
DOI: 10.1155/2019/1680269
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Mineral Oil Aromatic Hydrocarbons (MOAH) in Anhydrous Cosmetics Using 1H NMR

Abstract: In cosmetic products, hydrocarbons from mineral oil origin are used as ingredients in a wide variety of consistency, from liquid oil to solid wax. Refined mineral oil hydrocarbons consist of MOSH (mineral oil saturated hydrocarbons) and a low proportion of MOAH (mineral oil aromatic hydrocarbons). MOSH and MOAH comprise a variety of chemically similar single substances with straight or branched chains. In the context of precautionary consumer protection, it is crucial to determine hydrocarbons from mineral oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Another independent testing also demonstrated that a high number of lip care products (8/57, 14% of tested products) from the German retail trade contained high MOAH levels (0.4% to 1.6% w/w), similar to levels in mineral oils of technical quality. 12 Overall, the German BfR concluded from their global risk assessment based on a systematic literature review on mineral oils that no health risk for the consumer can arise from the cutaneous application of cosmetic products containing pharmaceutical-and food-grade mineral oils. 8 Moreover, health risks are not to be expected from oral intake of highly refined mineral oils, if lip care products comply with the recommendation of Cosmetics Europe.…”
Section: Rationale Of the Present Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Another independent testing also demonstrated that a high number of lip care products (8/57, 14% of tested products) from the German retail trade contained high MOAH levels (0.4% to 1.6% w/w), similar to levels in mineral oils of technical quality. 12 Overall, the German BfR concluded from their global risk assessment based on a systematic literature review on mineral oils that no health risk for the consumer can arise from the cutaneous application of cosmetic products containing pharmaceutical-and food-grade mineral oils. 8 Moreover, health risks are not to be expected from oral intake of highly refined mineral oils, if lip care products comply with the recommendation of Cosmetics Europe.…”
Section: Rationale Of the Present Articlementioning
confidence: 99%
“…Moreover, many lip care products contained >5% or >10% of MOSH with a chain length <C25, which is higher than the 5% recommended by Cosmetics Europe for lip care products, thus potentially exposing consumers to these more strongly absorbed MOSH. Another independent testing also demonstrated that a high number of lip care products (8/57, 14% of tested products) from the German retail trade contained high MOAH levels (0.4% to 1.6% w/w), similar to levels in mineral oils of technical quality . Overall, the German BfR concluded from their global risk assessment based on a systematic literature review on mineral oils that no health risk for the consumer can arise from the cutaneous application of cosmetic products containing pharmaceutical‐ and food‐grade mineral oils .…”
Section: Introductionmentioning
confidence: 99%